2011
DOI: 10.1021/ie200988g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nanocrystalline PbTiO3

Abstract: Nanocrystalline PbTiO3 in tetragonal form has been successfully prepared via a newly developed environmentally friendly coprecipitation process. The formation process of lead titanate from the PbC2O4·TiO2 precursor was monitored using DTA–TG, XRD, FT-IR, and TEM techniques. XRD showed the phase transition of less stable tetragonal PbO decomposition intermediate to a more stable orthorhombic structure by raising the calcination temperature. For the precursor calcined at 600 °C, only XRD lines characteristic of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Exclusively, strong absorption bands were noticed at 640 and 576 cm −1 which can be attributed to the stretching vibration of Ti−O and Ni−O. 35 Thus, the observed FT-IR spectra supports the formation of ilmenite NiTiO 3 nanorods.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…Exclusively, strong absorption bands were noticed at 640 and 576 cm −1 which can be attributed to the stretching vibration of Ti−O and Ni−O. 35 Thus, the observed FT-IR spectra supports the formation of ilmenite NiTiO 3 nanorods.…”
Section: ■ Results and Discussionmentioning
confidence: 60%
“…This behavior can be described based on increasing the mobility of charge carriers with increasing temperature. The conduction activation energy calculated is 0.73 eV which suggested that the hopping conduction mechanism is the predominant one [25]. The obtained low conduction energy suggests its using as semiconducting rectifiers.…”
Section: 6mentioning
confidence: 86%
“…The average grain size (d) of the particles was calculated from the formula: d=6/ρA; where ρ is the theoretical density of the material and A is the specific surface area of the powder [25].…”
Section: Characterizationmentioning
confidence: 99%
“…The sample showed a very broad FT-IR bands around 3441 and 1652 cm −1 assigned to the stretching vibration of O-H bond of water in hydrated zinc oxalate molecule. The vibration band at about 1302 cm −1 could be attributed to the symmetric mode of oxalate ion's carbonyl group [30]. The observed bands at 773 and 506 cm −1 are attributed to the out-ofplane and in-plane bending modes of water and O-C-O of oxalate, respectively while the band at 348 cm −1 could be assigned to the metal ion vibration [34].…”
Section: Ft-ir Spectroscopic Studymentioning
confidence: 94%
“…A new innovative route for the preparation of this precursors mixture was utilized in which, a stoichiometric amount of oxalic acid solution equivalent to precipitate zinc oxalate was added drop wise to the calculated amount of basic zinc carbonate and titania suspension under vigorous stirring at about 60 °C. After complete precipitation, the zinc oxalate is expected to precipitate on TiO 2 surface through heterogeneous nucleation [30]. The prepared precursors mixture was filtered, washed with distilled water, dried then given the name; as-prepared precursors mixture.…”
Section: Synthesis Processmentioning
confidence: 99%